2020
DOI: 10.1080/15387216.2020.1840414
|View full text |Cite
|
Sign up to set email alerts
|

“More-than-viral” Eurasian geographies of the covid-19 pandemic: interconnections, inequalities, and geopolitics

Abstract: This paper develops the notion of "more-than-viral" geographies of the covid-19 pandemic. It introduces a set of commentaries on the pandemic in the Eurasian region and its links with the rest of the globe. Taking "more-than-human" perspectives in Human Geography as an inspiration, it develops ways of analyzing the covid-19 pandemic as a "more-thanviral" phenomenon in which human and viral agencies are entangled. In this Introduction to the special issue, we focus on three key intertwined sets of processes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Others argue that COVID-19 itself mirrors and produces more inequalities of power and space, as well as socio-political conflicts within and among nations, regions, localities ( Dodds et al, 2020 ; also see the Special Issues in Dialogues in Human Geography , volume 20 Issue 2, and in Eurasian Geography and Economics , volume 61, Issue 4–5.). It is suggested that the state at multiple spatial levels has emerged as a key and powerful territorial agency on an unprecedented scale – through controlling global travel restrictions, domestic lock-down, social distancing and other measures – in creating an unconventional movement of geopolitics and socio-spatial governance ( Chan et al, 2020 ; Grundy-Warr & Lin, 2020 ). These studies have emphasized more on how the pandemic has been generating geographies of governance quality and performance mainly at the national level ( Asongu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Others argue that COVID-19 itself mirrors and produces more inequalities of power and space, as well as socio-political conflicts within and among nations, regions, localities ( Dodds et al, 2020 ; also see the Special Issues in Dialogues in Human Geography , volume 20 Issue 2, and in Eurasian Geography and Economics , volume 61, Issue 4–5.). It is suggested that the state at multiple spatial levels has emerged as a key and powerful territorial agency on an unprecedented scale – through controlling global travel restrictions, domestic lock-down, social distancing and other measures – in creating an unconventional movement of geopolitics and socio-spatial governance ( Chan et al, 2020 ; Grundy-Warr & Lin, 2020 ). These studies have emphasized more on how the pandemic has been generating geographies of governance quality and performance mainly at the national level ( Asongu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…23 Their arguments confirmed that a disease is a geopolitical issue, as Alan Ingram claimed in 2005. 24 Ingram concludes that, following the end of the Cold War, the disease has been seen as a geopolitical affair in terms of four main dimensions: destabilisation, sovereignty, the instrumen- 23 Sheikh et al 2021;Chan et al 2020;Markey 2020b;Ndlovu-Gatsheni 2020;Feyerabend 2020. 24 Ingram 2005 talisation of health, and the geopolitical economy.…”
Section: Geopoliticisation Of the Covid-19 Pandemicmentioning
confidence: 99%
“…The outbreak of Covid-19 forced governments and organizations to struggle in dealing with its implications. As a result, major changes emerged in various domains such as government (Shafi et al, 2020;Shah et al, 2020;Tolu et al, 2020), public services (Chen, 2020;Johnson et al, 2020), healthcare (Dewey et al, 2020;Mayer & Lewis, 2020), education (Mishra et al, 2020), transnational labour (Creţan & Light, 2020), geopolitical issues (Chan et al, 2020;Mionel et al, 2020;Moisio, 2020), global energy market (Connolly et al, 2020), spatial dimensions (Krzysztofik et al, 2020), and economy (Hammour et al, 2020;Kumar et al, 2020). The higher education sector was also subjected to adjustments and faced adverse challenges in its educational operations globally.…”
Section: Introductionmentioning
confidence: 99%